Prevalence of Child Sexual Abuse - Pakistan's Context - Khaliq, Jamshed; Rumman Iqbal Khattak, (Technium Social Sciences Journal, 2020)
The aim/ Objective of the study were to analyze the graph of child sexual abuse in Pakistan over the past ten years and to figure out the possible cause in prevalence of the same. Data for the said purpose was collected through Secondary source i.e. internet, newspapers, victims itself. Whereas, authentication of the data has been ensured through cross check from various other sources. CSA was found to be dominant mainly because of the silence of the victim, poor financial background, lack of strict implementation of rules & laws etc. Role of media has also been found to be an effective tool in prevention of this vicious act.